PENENTUAN KONDISI OPTIMUM HIDROLISIS PATI OLEH ASPERGILLUS NIGER DALAM LIMBAH KULIT KENTANG - Maria Tensiana Tima (AGRICA, 2018)
Determination of optimum condition for starch hydrolysis Aspergillus niger in shell potato waste. Shell Potato waste can be used as a raw material for making bioethanol because it contains carbohydrate ingredients, starch. The process of making bioethanol from starchy materials can be done through the hydrolysis process, then proceed with the fermentation process. The hydrolysis process is carried out to hydrolyze starch into glucose with the help of amylase enzyme produced from the Aspergillus nigerbacterium. This research was carried out at the Chemistry Laboratory of FMIPA Malang State University. The purpose of this study was to determine the optimum conditions for hydrolysis of starch from potato skin which includes temperature, pH, time and amount of Aspergillus niger used. The glucose level produced from the hydrolysis process is determined using the Somogy-Nelson method. The results showed that the optimum conditions for starch hydrolysis to produce optimum glucose levels were using 1.25 grams of Aspergillus niger (equivalent to 50 mL of culture), at pH 5 and temperature of 300C within 2 hours, with glucose produced as much as 0.0167 g of 100 g of shell potato waste flour.